Accountability and Learning: Exploding the Myth of Incompatibility bet ween Accountability and Learning - Guijt, Irene (NGO Management, 2010)
When accountability is understood as reporting on pre-deined deliverab les, it is often considered to be irreconcilable with learning. This c onventional wisdom inhibits an appreciation of their connection. In th is chapter, Irene Guijt exposes the laws and traps in reasoning that k eep accountability and learning apart. She provides practitioners with principles and basic good ideas that open up prospects for accountabi lity and learning to complement each other.